2021
DOI: 10.1093/jisesa/ieab084
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Cucurbit Chlorotic Yellows Virus (CCYV) on Biological Characteristics of Its Vector Bemisia tabaci (Hemiptera: Aleyrodidae) MED Species

Abstract: Plant viruses can change the phenotypes and defense pathways of the host plants and the performance of their vectors to facilitate their transmission. Cucurbit chlorotic yellows virus (CCYV) ( Crinivirus ), a newly reported virus occurring on cucurbit plants and many other plant species, is transmitted specifically by Bemisia tabaci MEAM1 (B biotype) and MED (Q biotype) cryptic species in a semipersistent manner. This study evaluated the impacts of CCYV on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Plant viruses can not only alter the phenotypes, nutritive values and defensive metabolites of their host plants, but also change the biological characteristics of insect vectors to promote virus transmission. [41][42][43][44][45] Previous studies have suggested that virusfree whiteflies prefer to feed on Tomato yellow leaf curl virus (TYLCV)-infected tomato plants, but viruliferous whiteflies lost their preference for TYLCV-infected plants, thus increasing the probability of virus transmission to uninfected host plants. 33 The current research showed a similar phenomenon in a semipersistent plant virus, which again confirms the vector manipulation hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Plant viruses can not only alter the phenotypes, nutritive values and defensive metabolites of their host plants, but also change the biological characteristics of insect vectors to promote virus transmission. [41][42][43][44][45] Previous studies have suggested that virusfree whiteflies prefer to feed on Tomato yellow leaf curl virus (TYLCV)-infected tomato plants, but viruliferous whiteflies lost their preference for TYLCV-infected plants, thus increasing the probability of virus transmission to uninfected host plants. 33 The current research showed a similar phenomenon in a semipersistent plant virus, which again confirms the vector manipulation hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 80% of the plant viruses depend on vectors for transmission. Infection by a virus may alter the phenotypic and volatiles of the host plants as well as the insect vectors' behaviors (He et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to earlier research (Jones 2003, Bragard et al 2013, Polston et al 2014, B. tabaci transmits more than 500 species of plant viruses from five families and five genera. Some of these viruses have seriously harmed agricultural production and resulted in financial losses (He et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in defensive biomolecules and increase in amino acids may be responsible for whitefly feeding preferences toward CCYV-infected hosts (Zhang et al, 2022). In other findings they suggest that CCYV can have a significant impact on the biological features of its vector, B. tabaci, assuming that CCYV and B. tabaci have formed a typical mutualist relationship mediated by host plants (He et al, 2021).…”
Section: General Introductionmentioning
confidence: 94%